Gastroprotective effect of plumbagin and ethanolic extract of plumbaginales in experimentally-induced ulcer - Sibi P. Ittiyavirah; Ann Shine Paul (Shahrekord University of Medical Sciences, 2016)
Introduction: Medicinal plants with phenolic compounds have been shown to have antimicrobial and antioxidant activities. The objective of the study was to evaluate the anti-ulcer effects of ethanolic extracts of Plumbaginales namely P. auriculata, P. indica and P. zeylanica and plumbagin in aspirin and ethanol induced gastric ulcer models. Methods: In vivo studies including DPPH scavenging assay, lipid peroxidase inhibition assay, acid neutralizing capacity test, aspirin- and ethanol-induced ulcer models were performed to assess the antioxidant and antiulcer effects of plants. By using the models of Aspirin (200 mg/kg, 1 hour after the administration of last dose of the extract/ranitidine) and ethanol (1 mL/200 g, 90%) induced ulcer, animals were randomly divided into three groups of six animals each. Group I served as positive control, group II acted as standard and received ranitidine (20 mg/kg). The group III was treated with ethanolic extract by oral route in a dose of 300 mg/kg for a period of 5 days. The animals were sacrificed and the stomach was then excised and cut along the greater curvature, washed carefully with 5.0 mL of 0.9% NaCl and ulcers were scored. Results: Both the aspirin- and ethanol-induced models of ulcer with various extracts of Plumbaginales showed significant acid neutralizing and antioxidant properties. Conclusion: This study suggests that root extracts of P. auriculata may have good quality potentials for use in peptic ulcer diseases and that P. auriculata possesses an antiulcer effect.